Detection Tuna and Processed Products Based Protein and DNA Barcoding - Nuring Wulansari; Mala Nurilmala; N. Nurjanah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Tuna is the second largest fishery commodity in Indonesia after the shrimp. Since thehigh demand and the limited stock of tuna resulted in fraudulent chance. Authenticationis required to meassure consumers regarding the accuracy of its labeling and foodsafety. In this study, the authentication was based on protein and DNA barcoding usingcytochrome-b gene (cyt-b) of the mitochondrial DNA as the target of gene. Primer ofcyt b gene was designed based on the tuna species. This study aimed to identify theauthenticity of tuna fresh and its processed products through protein using SDS-PAGE and DNA barcoding techniques. The phases of this research were protein electrophoresisby SDS-PAGE, DNA extraction, PCR amplification, electrophoresis and sequencing.Samples of fresh fish (Tu1, Tu2, Tu3, Tu4, and Tu5) and processed tuna (canned andsteak) were successfully extracted. Result showed that SDS-PAGE proved the damage ofproteins in the processed tuna, so this method was not appropriate if it is used to identifythe authenticity of tuna. PCR electrophoresis results showed that the samples of tuna,tuna steak, sushi, meat ball, abon, and caned tuna were successfully amplified in the rangeof 500-750 bp except Ka3, which was in line with the target of DNA (620 bp). Resultedsequences of Tu2, Tu3, Tu4 and Tu5 were identified according the results of morphometricnamely T. albacares, while Tu1 was identified as T. obesus with homology level of 99%.Processed tunas (steak and canned tuna) were identified as T. albacares, as stated on thelabels.Keywords: Authentication, cytb, DNA barcoding, design primer, SDS-PAGE